Across-Experiment Transcriptomics of Sheep Rumen Identifies Expression of Lipid/Oxo-Acid Metabolism and Muscle Cell Junction Genes Associated With Variation in Methane-Related Phenotypes - Xiang, Ruidong; McNally, Jody; Bond, Jude; Tucker, David; Cameron, Margaret; Donaldson, Alistair J.; Austin, Katie L.; Rowe, Suzanne; Jonker, Arjan; Pinares-Patino, Cesar S.; McEwan, John C.; Vercoe, Phil E.; et al. (Frontiers in Genetics, 2018)
Ruminants are significant contributors to the livestock generated component of the greenhouse gas, methane (CH4). The CH4 is primarily produced by the rumen microbes. Although the composition of the diet and animal intake amount have the largest effect on CH4 production and yield (CH4 production/dry matter intake, DMI), the host also influences CH4 yield. Shorter rumen feed mean retention time is associated with higher dry matter intake and lower CH4 yield, but the molecular mechanism(s) by which the host affects CH4 production remain unclear. We integrated rumen wall transcriptome data and CH4 phenotypes from two independent experiments conducted with sheep in Australia (AUS, n=62) and New Zealand (NZ, n=24). The inclusion of the AUS data validated the previously identified clusters and gene sets representing rumen epithelial, metabolic and muscular functions. In addition, the expression of the cell cycle genes as a group was consistently positively correlated with acetate and butyrate concentrations (p<0.05, based on AUS and NZ data together, same below). The expression of a group of metabolic genes showed positive correlations in both AUS and NZ datasets with CH4 production (p<0.05) and yield (p<0.01). These genes encode key enzymes in the ketone body synthesis pathway and included members of the poorly characterised aldo-keto reductase 1C (AKR1C) family. Several AKR1C family genes appear to have ruminant specific evolution patterns, supporting their specialised roles in the ruminants. Combining differential gene expression in the rumen wall muscle of the shortest and longest mean retention time AUS animals (no data available for the NZ animals) with correlation and network analysis, we identified a set of rumen muscle genes involved in cell junctions as potential regulators of mean retention time, presumably by influencing contraction rates of the smooth muscle component of the rumen wall. Higher rumen expression of these genes, including SYNPO (synaptopodin, p<0.01) and NEXN (nexilin, p<0.05), was associated with lower CH4 yield in both AUS and NZ datasets. Unlike the metabolic genes, the variations in the expression of which may reflect the availability of rumen metabolites, the muscle genes are currently our best candidates for causal genes that influence CH4 yield.